Another look through the microscope - Locally resolved electronic absorption spectra of silicate minerals measured in a microscope- spectrometer - Langer,K. (Journal of the Czech Geological Society, 2000)
Concepts of absorption spectroscopy in the UV/VIS/NIR and of excitations of electronic transitions in oxygen-based minerals in this spectral range are outlined. Absorption of energy in this range excites transitions in the electronic systems of ligands and central ion in polyhedra, LM-CT, in the electronic systems of two 3dN-ions with different valence and allocated in interconnected polyhedra, MM-CT and, finally, between energy states of the 3dN-ions themselves, dd-sa and dd-sf. Theoretical aspects of such transitions and their evaluation, to obtain much information useful in crystal chemistry and physics of minerals, is briefly sketched. To overcome difficulties related to the often occurring neccessity of scanning spectra on small crystals, small optically clear parts of larger crystals, or through small apertures of special devices as high-pressure DAC-cells, high-temperature cells etc., microscope-spectrometric methods were developed that are discussed here. They allow measurement on crystal spots down to about 5 µm in diameter, of polarized single-crystal spectra in the wide spectral range from 40000 to 5000 cm-1 (250 to 2000 nm) at ambient conditions and in a pressure range up to 20 GPa or at temperatures between about 100 and 900 °K. The paper presents examples of applications of such methods in the fields of mineral colour, band assignements in complex minerals by the study of chemically simple synthetic equivalents, of mineral analysis including Fe2+, Fe3+, of intra- and intercrystalline 3dN-ion distribution and of the analysis of local structural properties of 3dN-ion centered polyhedra. Local structural peculiarities cannot be elucidated by diffraction methods of structural research, as these methods are crystal averaging and do not individually see e.g. an 3dN-ion centered polyhedron in a mineral structure. In this field, the paper discusses the analysis of fO2-T-dependent formation of Fe3+-bearing point defects in fayalite and olivines. Here, the results can be used to estimate the oxygen fugacity of olivine formation in nature. Further, the evaluation of local mean 3dN-ion - ligand distances of individual 3dN-ion centered polyhedra, and determinations of polyhedral compression as well as polyhedral thermal expansion are dealt with.
Keywords: Microscope-spectrometry; silicate minerals; electronic transitions; local structural properties; ligand-field theory